2020
DOI: 10.3390/vetsci7040168
|View full text |Cite
|
Sign up to set email alerts
|

On the Importance of the Sound Emitted by Honey Bee Hives

Abstract: Recent years have seen a worsening in the decline of honey bees (Apis mellifera L.) colonies. This phenomenon has sparked a great amount of attention regarding the need for intense bee hive monitoring, in order to identify possible causes, and design corresponding countermeasures. Honey bees have a key role in pollination services of both cultivated and spontaneous flora, and the increase in bee mortality could lead to an ecological and economical damage. Despite many smart monitoring systems for honey bees an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 48 publications
1
24
0
3
Order By: Relevance
“…It has been shown that the bee activity acoustic monitoring accuracy could be improved further in this way. The achieved accuracy was comparable to results of other systems with similar complexity [20,23,25,26]. The hidden layer parameter variation also influenced the complexity of the acoustic models.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…It has been shown that the bee activity acoustic monitoring accuracy could be improved further in this way. The achieved accuracy was comparable to results of other systems with similar complexity [20,23,25,26]. The hidden layer parameter variation also influenced the complexity of the acoustic models.…”
Section: Discussionsupporting
confidence: 71%
“…Convolutional neural networks with MFCC features were used by the authors in [22]. A more detailed review of bee activity acoustic analysis literature can be found in [26].…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…We are all familiar with the buzz of bee wings, which is typically at 270 Hz. At other times one can hear intermittent sounds, such as queen bees tooting (550 Hz) or quacking (300 Hz), or workers piping (400 Hz) [7][8][9]. Most bee sounds are well below 600 Hz.…”
Section: Prior Workmentioning
confidence: 99%